In vitro inhibitory activities of selected Australian medicinal plant extracts against protein glycation, angiotensin converting enzyme (ACE) and digestive enzymes linked to type II diabetes. Issue 1 (December 2016) - Deo, Permal; Hewawasam, Erandi; Karakoulakis, Aris; Claudie, David; Nelson, Robert; Simpson, Bradley; Smith, Nicholas; Semple, Susan
Abstract Background There is a need to develop potential new therapies for the management of diabetes and hypertension. Australian medicinal plants collected from the Kuuku I'yu (Northern Kaanju) homelands, Cape York Peninsula, Queensland, Australia were investigated to determine their therapeutic potential. Extracts were tested for inhibition of protein glycation and key enzymes relevant to the management of hyperglycaemia and hypertension. The inhibitory activities were further correlated with the antioxidant activities. Methods Extracts of five selected plant species were investigated:Petalostigma pubescens, Petalostigma banksii, Memecylon pauciflorum, Millettia pinnata andGrewia mesomischa. Enzyme inhibitory activity of the plant extracts was assessed against α-amylase, α-glucosidase and angiotensin converting enzyme (ACE). Antiglycation activity was determined using glucose-induced protein glycation models and formation of protein-bound fluorescent advanced glycation endproducts (AGEs). Antioxidant activity was determined by measuring the scavenging effect of plant extracts against 1, 1-diphenyl-2-picryl hydrazyl (DPPH) and using the ferric reducing anti-oxidant potential assay (FRAP). Total phenolic and flavonoid contents were also determined. Results Extracts of the leaves ofPetalostigma banksii andP. pubescens showed the strongest inhibition of α-amylase with IC50 values of 166.50 ± 5.50 μg/mL and 160.20 ± 27.92 μg/mL, respectively. TheP. pubescens leaf extract was also the strongest inhibitor of α-glucosidase with an IC50 of 167.83 ± 23.82 μg/mL. Testing for the antiglycation potential of the extracts, measured as inhibition of formation of protein-bound fluorescent AGEs, showed thatP. banksii root and fruit extracts had IC50 values of 34.49 ± 4.31 μg/mL and 47.72 ± 1.65 μg/mL, respectively, which were significantly lower (p  < 0.05) than other extracts. The inhibitory effect on α-amylase, α-glucosidase and the antiglycation potential of the extracts did not correlate with the total phenolic, total flavonoid, FRAP or DPPH. For ACE inhibition, IC50 values ranged between 266.27 ± 6.91 to 695.17 ± 15.38 μg/mL. Conclusions The tested Australian medicinal plant extracts inhibit glucose-induced fluorescent AGEs, α-amylase, α-glucosidase and ACE with extracts ofPetalostigma s pecies showing the most promising activity. These medicinal plants could potentially be further developed as therapeutic agents in the treatment of hyperglycaemia and hypertension.